Meningkatkan Kemampuan Kognitif Pendidikan Pancasila Dan Kewarganegaraan (PPKN) Materi Perumusan Dan Penetapan Pancasila Sebagai Dasar Negara Melalui Model Pembelajaran Think Pair Share - Titussiana Titussiana (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Based on the study results, it was found that several factors were the cause of the low cognitive abilities of students in learning Pancasila and Citizenship Education (PPKn), the material for the formulation and stipulation of Pancasila as the basis of the state. The first factor is that students are not actively involved in learning activities. Students act more as passive recipients of information, not as subjects who carry out learning activities, so students' attention is often diverted to other things outside the subject matter even though learning activity facilities are good. The objectives of this study, among others: To determine the implementation of the think pair share learning model for students. To determine the cognitive abilities of Pancasila and Citizenship Education (PPKn), the material for the formulation and stipulation of Pancasila as the basis of the state. To find out the implementation of the think pair share learning model can improve the cognitive ability of Pancasila and Citizenship Education (PPKn), the material for the formulation and stipulation of Pancasila as the basis of the state. Based on the results of the study, it can be seen that students' cognitive abilities by implementing the think pair share learning model from cycle I to cycle II continue to experience a significant increase, namely from an increase in the average value of cognitive abilities of 76.92 then an increase in cycle II is of 81.48. So there is an increase in the value of cognitive abilities of 4.56. Thus, the cognitive ability of Pancasila and Citizenship Education (PPKn) material for the formulation and determination of Pancasila as the basis of the state obtained by students has increased significantly after the think pair share learning model was implemented.